Coastal communities’ participation in reducing single-use plastic bags: the role of awareness of harm and responsibility for environmental protection - Huy Van Le; Le Chi Cong; Mark A.A.M. Leenders (Journal of Trade Science)
Purpose – This research aims to explore the role of awareness of harm and responsibility for environmental protection in reducing pollution from single-use plastic bags (SPBs) in coastal communities (CCs). To this end, this study develops and tests a unique model that explains residents’ intention to reduce the use of SPBs in coastal regions. Design/methodology/approach – A questionnaire was used to collect data from 721 coastal residents in Vietnam. Structural equation modeling and moderation analysis were applied to test the proposed hypotheses. Findings – The results show that awareness of the impact of SPBs on the environment and human health and awareness of the responsibility to protect the coastal environment significantly affect attitudes and intentions to reduce the use of SPBs. Moreover, such awareness of responsibility strengthens the attitude-intention relationship. Practical implications – The findings suggest that CCs should not receive a lower priority in campaigns and efforts to reduce SPBs. In this regard, providing residents with free environmentally friendly bags and education programs on the impact of SPBs could be implemented. Originality/value – CCs are directly impacted by pollution from SPBs. However, little is known about how this affects their polluting behavior. This study shows that CCs are not immune to polluting behaviors and that SPBs can be significant among residents. It also demonstrates that awareness of harm and feeling responsible for the environment are essential drivers of (intended) sustainable behaviors.